Reconstructing Qur’anic Social Justice: A Contextual Analysis of QS. An-Nisa Verse 135 in Tafsir An-Nur - Muh. Imam Sanusi Al Khanafi; Rizky Pratama Putra (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2026)
This study aims to reconstruct the concept of Qur’anic social justice through a contextual analysis of Surah An-Nisa (4):135 in Tafsir An-Nur by Hasbi Ash-Shiddieqy. Social justice is a fundamental value in Islam that requires the enforcement of justice objectively without discrimination. Yet, its implementation in modern Indonesia still faces challenges such as economic inequality and weak legal integrity. This research employs a qualitative method with a library research design and a thematic-contextual tafsir approach. The primary data source is Tafsir An-Nur, while secondary data are drawn from relevant literature. The findings indicate that Hasbi interprets Surah An-Nisa (4):135 as a command to uphold justice consistently (qawwāmīn bil-qisṭ) regardless of social status, economic condition, or personal relationships. This interpretation emphasizes that justice in Islam is universal, transformative, and oriented toward social welfare. Contextually, these values are relevant to legal reform, reducing economic inequality, and strengthening democracy and tolerance in Indonesia. Therefore, Tafsir An-Nur contributes to contextualizing Qur’anic justice as an ethical foundation for modern social life.